2022
DOI: 10.1007/s12072-022-10339-2
|View full text |Cite
|
Sign up to set email alerts
|

Gamma knife radiosurgery versus transcatheter arterial chemoembolization for hepatocellular carcinoma with portal vein tumor thrombus: a propensity score matching study

Abstract: Background The optimal locoregional treatment for hepatocellular carcinoma (HCC) patients with portal vein tumor thrombus (PVTT) is unclear. This study aimed to investigate the efficacy of Gamma knife radiosurgery (GKR) versus transcatheter arterial chemoembolization (TACE) in HCC patients with PVTT. Methods This retrospective study included 544 HCC patients with PVTT (GKR, 202; TACE, 342). Propensity score matching (PSM) analysis identified 171 matched pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 36 publications
(48 reference statements)
2
15
0
Order By: Relevance
“…In addition, most of the patients we studied at our hospitals were treated with GRK as the RT modality. Treatments of the non-RT group included TACE, and our results showed that RT had superior e cacy to TACE and other treatments in this group of patients, which is consistent with ndings from the previous study by Su et al 17 .…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In addition, most of the patients we studied at our hospitals were treated with GRK as the RT modality. Treatments of the non-RT group included TACE, and our results showed that RT had superior e cacy to TACE and other treatments in this group of patients, which is consistent with ndings from the previous study by Su et al 17 .…”
Section: Discussionsupporting
confidence: 92%
“…In addition, Lu et al rst reported that the combination of TACE plus GKR was well tolerated and produced overall survival (OS) bene ts in HCC patients with portal vein tumor thrombosis (PVTT) 13 . And in our previous study, Su et al proved that GKR had better OS compared with TACE in HCC with PVTT (17.2 vs. 8.0 months, p < 0.001) 17 . RT is an evolving technique for HCC, and it should receive more attention.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“… 34 In addition, Su et al confirmed that gamma knife radiosurgery has a superior OS compared to TACE in the treatment of PVTT-HCC. 35 Predicting the prognosis of HCC patients remains a formidable obstacle, despite the widespread use of numerous treatment methods in clinical practice. In our subgroup analysis based on various treatment modes, the ALP and LDH groups with low expression and the ALP and LDH groups with high expression exhibited superior OS.…”
Section: Discussionmentioning
confidence: 99%
“…A high probability of tumor transfer via the portal vein before liver resection could lead to a high likelihood of persistent tumor cells after LR in HCC patients with PVI, HCC complicated with MVI is prone to have residual cancer cells after hepatectomy, making the chemotherapy more evident. It was reported that gamma knife radiosurgery and transcatheter arterial chemoembolization had different survival effect for patients with HCC depending on the type of portal vein tumor thrombus (PVTT) [ 33 ]. Hence, it would be better to evaluate the efficacy of HAIC for HCC patients based on the type of PVTT in further research.…”
Section: Discussionmentioning
confidence: 99%